Thyroplasty under Conscious Sedation using Dexmedetomidine: A Case Series - Raj Murugan; Sathyasuba Meenakshisundaram; Gayathri Ramesh; Raghuraman M Sethuraman (Düzce Tıp Fakültesi Dergisi)
Thyroplasty is a surgical procedure done on the thyroid cartilage to improve voice quality and is performed only in a few centers. Either peri-operative voice testing or confirming the vocal cord movements with a fiberoptic bronchoscope (FOB) visualization can be used as a guide to enhance the results in such cases. The anesthetic implications in such cases are less frequently reported. The published reports are mainly case series or retrospective analyses where cases were done under general anesthesia or deep sedation. This study aimed to present a series of thyroplasty cases wherein both voice testing and confirming the vocal cord movements with FOB visualization were done under conscious sedation, achieving a stable plan of sedation with dexmedetomidine infusion. Conscious sedation with dexmedetomidine as the sole agent for the maintenance of sedation can be safely adopted for these procedures.